Error-Constrained Fixed-Time Dynamic Positioning of MSV With Saturated Event-Triggered Inputs - Li, Jinjiang; Xiang, Xianbo; Dong, Donglei; Yang, Shaolong (IEEE transactions on intelligent transportation systems, 2024)
This paper addresses the fixed-time event-triggered dynamic positioning (DP) problem of a marine surface vehicle (MSV) subject to external disturbance, input saturation, and position error constraints. First, a performance function with self-adjusting capability is proposed to enhance the controller's adaptability to diverse initial conditions and mitigate the occurrence of control singularities resulting from error fluctuations triggered by sudden disturbances. Then, guidance kinematic laws are developed using the universal barrier function (UBF) technique to constrain distance and orientation errors and address the fragility problem associated with existing prescribed performance controllers. Subsequently, low-complexity fuzzy approximators and constrained auxiliary signals are employed at the kinetic design level to eliminate the negative effect of unknown hydrodynamic functions and input saturation. Finally, smooth switching signal-based dynamic event-triggered kinetic control laws are developed to minimize the working frequency of actuator and prevent large control transitions. Theoretical analysis confirms that all signals in the closed-loop system are bounded, and the Zeno behavior can be averted. Simulation results further demonstrate the effectiveness of the proposed controller.